2002
DOI: 10.1124/mol.61.4.832
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Rat Organic Anion Transporting Polypeptide 2 by Pregnenolone-16α-carbonitrile Is via Interaction with Pregnane X Receptor

Abstract: The rat organic anion transporting polypeptide 2 (oatp2; Slc21a5) is a liver transporter that mediates the uptake of a variety of structurally diverse compounds, and has a high affinity for cardiac glycosides. Treatment of rats with pregnenolone-16␣-carbonitrile (PCN), a ligand for the rodent pregnane X receptor (PXR), significantly enhances the rat oatp2 gene expression. To understand the molecular mechanism of oatp2 induction by PCN, rat oatp2 gene was cloned. The rat oatp2 gene consists of 16 exons; alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 32 publications
4
66
0
1
Order By: Relevance
“…In addition to up-regulation of some transporters, PCN administration also decreased Cnt2 mRNA in jejunum and ileum of WT mice, but not in PXR-null mice, indicating that the decrease is mediated via PXR. Regulation of rat and mouse hepatic Oatp1a4 (Staudinger et al, 2001a;Guo et al, 2002c) and Mrp3 (Teng et al, 2003), as well as mouse intestinal Mdr1a (Geick et al, 2001;Matheny et al, 2004) by PCN, has been reported previously. The present study confirms that mouse hepatic Oatp1a4 and Mrp3, and intestinal Mdr1a regulation by PCN is PXR-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to up-regulation of some transporters, PCN administration also decreased Cnt2 mRNA in jejunum and ileum of WT mice, but not in PXR-null mice, indicating that the decrease is mediated via PXR. Regulation of rat and mouse hepatic Oatp1a4 (Staudinger et al, 2001a;Guo et al, 2002c) and Mrp3 (Teng et al, 2003), as well as mouse intestinal Mdr1a (Geick et al, 2001;Matheny et al, 2004) by PCN, has been reported previously. The present study confirms that mouse hepatic Oatp1a4 and Mrp3, and intestinal Mdr1a regulation by PCN is PXR-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited availability of good antibodies and specific substrates for each transporter, regulation of transporters has mainly been determined at the mRNA level. However, the increase in expression of Oatp1a4 mRNA correlates with a marked increase in clearance of ouabain by the liver (Klaassen, 1974b;Eaton and Klaassen, 1978;Guo et al, 2002c).…”
Section: Discussionmentioning
confidence: 99%
“…39 Subsequent studies have shown that potentially cholestatic bile salts, including deoxycholate, may also activate PXR. 12,40 PXR in turn induces proteins of phase I metabolism (e.g., CYP3A) and hepatic transporters 11,41 (Mdr P-glycoprotein, Oatp2), resulting in the detoxification and elimination of toxic bile salts and xenobiotic substances. In the present study, we show that Oatp2 expression was increased after CA feeding in the rat, which is in contrast to the observed down-regulation of Ntcp, Oatp1, and Oatp4.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, largely due to increasing hormonal levels, the hepatic expression of PXR increases by approximately 20-fold during the perinatal period in mice (Masuyama et al, 2001). PXR-mediated induction of Cyp3a and several key ABC drug efflux transporters in liver such as Mdr1, Mrp2, Mrp3, and Bcrp has been demonstrated (Guo et al, 2002;Kliewer et al, 2002;Teng et al, 2003;Anapolsky et al, 2006). Likewise, PXR activation has been found to induce expression and activity of P-gp at the blood-brain barrier (Bauer et al, 2004(Bauer et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%